OPTIMIZATION PROBLEMS OF WINTER WHEAT CROP DАTES IN ALTITUDE ZONES IN THE REPUBLIC OF ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2010)
The aim of the paper is to analyse and evaluate maturity of winter wheat climatic conditions of the autumn period as well as to determine the optimal dates of wheat crop in the altitude zones of the RA. The optimal dates of the winter wheats determinate as the day or ten days period, when in autumn the average air temperature becomes less than 15℃, and the vegetation discontinues, when air temperature becomes less than 5℃.
Keywords: winter wheat crop; optimal dates of the winter wheats; vegetation\; vegetation